Evaluating the Bacterial Contamination in Used Cosmetic Products: A Potential Threat to Consumer’s Health - Rakhshanda Abbasi; Shaista Bano; Tunio, Sarfraz Ali; Nazir Ahmed Brohi; Aasma Siddiqui (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Cosmetic products tend to be prone to microbial contamination as they contain growth factors, essential minerals, organic and inorganic compounds which provide favourable conditions for microbial growth. The aim of the present study is to evaluate the bacterial contamination in used cosmetic products at Hyderabad. A total of 22 samples of used cosmetic products belonging to Mascaras and Eyeliners were collected from beauty salons and homes, which were either used by a single person or used in sharing with other family members. The isolation and identification of contaminating bacteria was carried out on the basis of cultural, morphological, and biochemical characteristics. Out of 22 cosmetic samples 72.73% (n = 16) demonstrated bacterial growth, while 27.27% (n = 6) samples had no bacterial growth. A total of n = 41 bacterial isolates were recovered from used cosmetic samples. The majority of bacteria belonged to Gram-positive 82.93% (n = 34) while 7.32% (n = 03) were Gram-negative bacteria. Moreover, 9.76% (n = 04) samples showed the growth of mixed cultures. Bacteriological profiling revealed that Bacillus spp. were dominant with 63.41% (n = 26), followed by Micrococcus spp. 7.32% (n = 03), Coagulase-negative Staphylococci 7.32% (n = 03), Staphylococcus aureus 4.88% (n = 02), while Proteus mirabilis 2.44% (n = 01), Citrobacter spp. 2.44% (n = 01), E. coli 2.44% (n = 01). Our results have shown that, the shared cosmetics whether used at homes or in salons were more prone to bacterial contamination than non-shared home-based single users, suggesting that sharing increases their susceptibility to bacterial contamination, which can spread bacteria and cause skin infections.